Agama dan Pengaruhnya terhadap Pisikologi Masyarakat Islam dan Kristen di Desa Tanjung Parapat Kec. Laut Tador Kab. Batu Bara - Saragih, Ayu Ulfa Mahdani; Harahap, Aprilinda M.; Ginting, Ernawati Beru (Darul Yasin Al Sys, 2023)
Religion is something that can change a person's behavior because religion contains rules that can lead a person in a better direction. Because, every religion must have certain purposes so that its adherents become more focused. In Tanjung Parapat Village, people consider religion to be just a rule that makes life difficult, so gambling, drinking and drugs are considered normal, the main factor is the lack of understanding of religion in society. From the problem formulation above, this research aims to inform the public that religion not only exists but also has an influence on life and the soul or human psychology. This research uses a qualitative method, which is a research carried out by collecting data by examining locations where there are symptoms that will be examined to find facts that exist in society. Based on the author's research that has been carried out and obtained findings that religion has an active role in religious, social values, harmony as learning in life. And the research results can be concluded that religion is not just a ritual, but religion functions to form moral values, creed values, which can be used as learning in people's lives.